2003
DOI: 10.1897/1551-5028(2003)022<0302:attods>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Toxicity of Dodecylbenzene Sulfonate to the Midge Chironomus Riparius Using Body Residues as the Dose Metric

Abstract: Dodecylbenzene sulfonate (DBS) is a component of linear alkylbenzene sulfonate (LAS), an anionic surfactant, mainly used in household detergents. Due to the large quantity of DBS in use, there is concern over adverse environmental effects. This work examined the toxicokinetics and toxicity of the 2-phenyl isomer of dodecylbenzene sulfonate in 4-d, 10-d, and partial life-cycle tests on the midge, Chironomus riparius, exposed to aqueous solutions. Toxicokinetics were determined in 10-d uptake and 5-d elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…2). This difference between the estimate using residues from live versus dead organisms is different than that observed for PCBZ [12] and for dodecylbenzene sulfonate [26] where the two methods for determining the mean lethal residue resulted in similar values. No direct method exists for evaluating the relationship between the LR50 values and the two methods of measuring the MLR50 because the exposure times differ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This difference between the estimate using residues from live versus dead organisms is different than that observed for PCBZ [12] and for dodecylbenzene sulfonate [26] where the two methods for determining the mean lethal residue resulted in similar values. No direct method exists for evaluating the relationship between the LR50 values and the two methods of measuring the MLR50 because the exposure times differ.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that the LR50 values are the same whether calculated from body residues measured in live or dead organisms [12,26]. This is likely the case because the organisms have similar toxicokinetics until death and demonstrated by similarities in the bioconcentration factors in live and dead organisms for pentachlorobenzene [12].…”
Section: Discussionmentioning
confidence: 99%
“…The critical body residue approach for expressing toxic levels of contaminants has been used as an alternative to sediment concentration-based approaches, because it potentially improves the interpretation of toxicity by considering bioavailability, differing feeding behaviors among species, accumulation kinetics, and the effects of biotransformation (e.g., [53]). This approach assumes that the tissue concentrations of a contaminant associated with toxic effects (e.g., mortality) are similar irrespective of exposure pathways or bioavailability or compound bioavailability in the exposure media.…”
mentioning
confidence: 99%
“…Tissue residue information can be helpful in understanding otherwise problematic situations exemplified by the wide range of acute‐chronic ratios (Kenaga 1982). Thus, the use of tissue residues allows development of dose‐response spectra; that is, the range of residues associated with a range of responses graded by severity (e.g., Hwang et al 2001, 2003, 2004; Schuler et al 2007a, 2007b).…”
Section: Addressing Key Issues With the Tissue Residue Approachmentioning
confidence: 99%